Franco Ferrarotti and the Challenges of the Social Research - Exploring the Dimensions and Definitions of Research in Social Sciences in Addressing Major Quests on the Individual and Society - Arta Musaraj (Academicus International Scientific Journal)

(untitled)
The paper analyses the role and impact of Franco Ferrarotti in defining the nature, boundaries and methods of modern sociology. Considered as the “founder of the Italian sociology”, Ferrarotti definitively represented a strong contributor in shaping the definition, methodology and practices of the modern sociology, a science capable to understand, address and forecast today’s global societies challenges and dialectics. The discussion on the role of scientific research in the social development of todays and tomorrow’s humanity, the attention that must be given on the duality between knowledge and conscience as a marker of this development, is a rare inherence Ferrarotti left to all researchers of our times who deal with the individual and its behavior, its social interactions, the world they create and the future orientation of mankind.